Isu dan cabaran pekerjaan orang kurang upaya penglihatan di Malaysia - Hammad Mohd Saidi; Aizan Sofia Amin; Nur Saadah Mohamad Aun; Mohd Nasir Selamat; Mohd Iqbal Haqim Mohd Nor (Penerbit Universiti Kebangsaan Malaysia, 2018)
This article aims to explore the employment issues of persons with visual impairment in Malaysia. Based on analysis of the literature reviews, there are two main employment issues faced by persons with visual impairment in Malaysia, namely job opportunity and workplace issues. These issues caused significant dilemmas for persons with visual impairment to work and they give negative implications on their social functioning and career development. In addition, challenges such as impairment effects, age, gender, level of education, vocational training and skills, family, employers’ negative attitudes, transportation, lack of policy enforcement and non-conducive environment in the workplace become the main factors that contribute to the employment issues. Therefore, this article discusses the suggestion for a suitable conceptual framework and methodology that can be used for future research.